Cartographic modeling of transport accessibility of territorial community centers in the Sumy region - Kornus, Anatolii; Kornus, Olesia (Human Geography Journal, 2025)
The article presents the results of a study on the transport accessibility of district centers in the Sumy region using mathematical modeling and geoinformation analysis methods. Based on graph theory, a model of the region's transport network was developed, where settlements were considered as nodes and road connections as weighted edges of the graph. Dijkstra’s algorithm was used to calculate the shortest paths and travel time accessibility. The obtained travel time values from district centers to peripheral settlements were interpolated to construct isochrone maps, allowing for an assessment of the spatial heterogeneity of transport provision in the region.The analysis revealed significant geographical differences in transport accessibility levels across the districts. The best accessibility indicators are observed in areas close to the regional center, while peripheral communities, particularly in the Konotop and Shostka districts, are characterized by substantial travel time costs to reach district centers.Special attention is given to territorial contrasts in transport accessibility, which are determined by the spatial structure of the road network and the administrative-territorial features of the region. The use of Python and Google Colab for calculations and visualization enabled efficient modeling and analysis of the region's transport system. The research findings may be useful for spatial planning, optimizing road infrastructure, and improving population mobility within administrative districts.